Kepemimpinan Inklusif sebagai Determinan Perilaku Kerja Inovatif: Peran Mediasi Martabat Ditempat Kerja - Aan Jeffri; Ririn Handayani; Adolf Bastian (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
The study was conducted at PT. PLN (Persero) to examine the role of workplace dignity in mediating the influence of inclusive leadership on innovative work behavior. The study population consisted of 890 people. Based on this population size, as per the Krejcie and Morgan (1970) table, the sample size for this study was 269 people. The sampling method used in this study was Systematic Random Sampling. All respondents were used to obtain primary data related to the variables, which were collected through a questionnaire with a 1-5-point Likert scale. All data obtained were analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. This study found that inclusive leadership had a significant positive effect on innovative work behavior; inclusive leadership had a significant positive effect on workplace dignity; workplace dignity had a significant positive effect on innovative work behavior; and workplace dignity mediated the effect of inclusive leadership on innovative work behavior.